2007
DOI: 10.1183/09031936.00025107
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide abrogates acute lung injury caused by ischaemia/reperfusion

Abstract: Poly (ADP-ribose) synthase or polymerase (PARS and PARP, respectively) is a cytotoxic enzyme which causes cellular damage. Nicotinamide, a compound of vitamin B complex, has been reported to exert an inhibitory effect on PARS or PARP. The present study tests the effects of nicotinamide on acute lung injury and associated alterations following ischaemia/reperfusion (I/R) of the isolated perfused rat's lung.I/R increased the lung weight (LW) to body weight ratio, LW gain, protein and dye tracer leakage, pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Previous studies have reported that niacinamide exerts protective effects on the acute lung injury induced by various challenges including endotoxin, ischemia/reperfusion, and oxidative stress [7,9,20,35-38]. In the present investigation, we found that this cytoprotective agent effectively abrogated the lung injury caused by phorbol myristate acetate in isolated lungs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have reported that niacinamide exerts protective effects on the acute lung injury induced by various challenges including endotoxin, ischemia/reperfusion, and oxidative stress [7,9,20,35-38]. In the present investigation, we found that this cytoprotective agent effectively abrogated the lung injury caused by phorbol myristate acetate in isolated lungs.…”
Section: Discussionsupporting
confidence: 67%
“…NAC was given simultaneously with PMA [20,37,38]. Examinations of biochemical factors were taken before administration of PMA and NAC, and at the end of the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…As such, supplementation may be useful over a broad range of metabolic disorders. In the clinical setting, niacinamide is used primarily for the treatment of acne and pellagra; however, niacinamide has also been studied in insulin-dependent diabetes, where it may preserve pancreatic ␤ cells (12), and ischemia-reperfusion injury, where it inhibits nitric oxide synthase (13). Niacinamide may mediate a variety of protective mechanisms through downregulation of TNF-␣ (14), increased free radical scavenging (15), and inhibition of poly-ADP-ribose synthetase, an emerging target for cardiovascular disease and cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Allografted airways treated with INO-1001 demonstrated attenuated NF-B nuclear translocation and reduced transcription of tumour necrosis factor (TNF)-, indicating proinflammatory effects of PARP-1 activation [60]. Recently, Su et al [61] have demonstrated elevated levels of poly-ADP-ribose in the lungs following I/R. Moreover, nicotinamide reduced the expression of inducible nitric oxydase synthase (iNOS) and pro-inflammatory cytokines, as well as the levels of nitric oxide (NO) and free radicals, while restoring ATP levels.…”
Section: Parp-1 In Lung Disordersmentioning
confidence: 99%
“…Moreover, nicotinamide reduced the expression of inducible nitric oxydase synthase (iNOS) and pro-inflammatory cytokines, as well as the levels of nitric oxide (NO) and free radicals, while restoring ATP levels. These effects were suggested to be due to PARP-1 inhibition [61].…”
Section: Parp-1 In Lung Disordersmentioning
confidence: 99%